A methodology for equipment condition simulation and maintenance threshold optimization oriented to the influence of multiple events. (January 2023) - Jin, Yuxue; Geng, Jie; Lv, Chuan; Chi, Ying; Zhao, Tingdi
Highlights: A methodology of equipment condition simulation (EQS) is presented. A maintenance threshold optimal model (MTOM) based on EQS is presented. The EQS oriented to multi-events influence can be more accordance with reality. The MTOM improves the accuracy of long-term prediction to a certain extent. Abstract: The core of condition-based maintenance is the accurate evaluation of equipment state. For various equipment, performance degradation or regression caused by factors, such as unexpected shock, failure, and work stress withdrawal, is typical. Accordingly, the law on incorporating impulse, failure, maintenance, and regression events based on natural condition evolution is analyzed. Moreover, a mathematical model and simulation algorithm of equipment condition evolution are devised. Then, considering safety, availability, and economy, the optimal maintenance threshold is determined based on the condition evolution process, providing new technical support to the field of maintenance decision-making. Finally, the effectiveness of the proposed model and algorithm is proved. The improved conformance of the stochastic process to actual situations considering the influence of multiple events is thus demonstrated. Further, a new concept for equipment maintenance management is presented.